PENGARUH KOMITMEN ORGANISASIONAL DAN STRES KERJA TERHADAP PERILAKU KEWARGANEGARAAN ORGANISASIONAL PADA KARYAWAN EVENT ORGANIZER DI SURABAYA - Candra, Candra Lourencia; Wulani, Fenika; Suhartatik, Ani (Universitas Katolik Widya Mandala Surabaya, 2017)
Human resources are a resource that has its own characteristics because it has emotions and thoughts. Emotions and thoughts that arise can affect employee job satisfaction and employee loyalty level of employment as human resources. Therefore, this study aims to analyze and obtain empirical evidence of the influence of empowerment and workplace environment to job satisfaction and employee’s job loyalty. This research is a quantitative research with three hypotheses to be tested. The sample used in this study are 200 respondents who are employees of MSMEs in Madura and Surabaya. Relevant data in this research are 50 data from 200 respondents to be processed. Independent variables used are employee empowerment and workplace environment, the first dependent variable is job satisfaction and second dependent variable that is employee work loyalty. The results of the tested on the employees of MSME showed that the two independent variables have a positive effect on the first dependent variable and the first dependent variable also positively affects the second dependent variable